Atribuições do farmacêutico na atenção primária à saúde - Diana Martins Barbosa (2009)
The creation of Sistema Único de Saúde, Brazilian public health system,established a group of assistencial actions to be proffed in a universal and a fair way, organized in a regionalized and hierarchy way, with the scope definition of each between federal. The Primary Health Care belongs, than, to the municipal district. In this process the medicine questions have been discussed and, in spite of changes that has happening, the pharmacist still has a small insertion on thehealth team. In this way the purpose of the study is to establish the profile of the pharmacist responsibilities and activities when acting in the Minas Gerais Primary Health Care. It was made, by postal survey, a work process evaluation in its three dimensions: technical, institutional and of interpersonal relationships. There were sent 562 questionnaires to 462 cities, according to the number of pharmacists presented in the National Health Establishment Register and in the Minas Gerais First Census of Human Resources in Primary Health Care (2006). The questionnaires were sent to the professional by postal service and e-mail. The 88variables were divided in three groups: professional identification, work features and activities features. The last one was subdivided in Medicine Management Technologies (classified as classic use and the review of the REMUME, partcipation of the medicine purchase process, inventory control, receiving, storage and medicine validity conference and non-classic CFT participation, issue of thechnical advice to the purchasing process and dispensing and storage of all medicines in the pharmacy), Medicine Use Technologies, Sources of medicine information and seven thematic groups. The responses rate was 29%. Most of the professional were female and 45,9% were younger than 30 years old.Slightly more than half (52,3%) were graduated in a public university and 35,2% has more than 10 years graduated. Considering work features, 87,1% of the pharmacists worked in only one city and the health basic unit was the most frequently work place; 41,1% worked in the same pace from 1 to 5 years and 54,8% earn from R$ 1.000,00 to R$ 2.000,00. The classic Management Technologies activities presented high rates of answers confirming its accomplishment, while to the non-classic the responses rates were lower and variable. To the Medicine Use Technologies activities the rates for non-completion were the highest. The obtained results propose that the Management Technologies activities, related to security medicine supply and accessibility,remain as the main pharmacists activities. In other hands, the Use Technologies, related to the guaranties to the intervention correct outcomes and to the rational medicine use, is being healed in a smaller proportion by the pharmacist. There is still a low degree of uniform pharmacist behavior in the non-classic Management Technologies and in the Medicine Use Technologies. It features lot of difficultiesto the definition of a pharmacist identity considering the assistencial activities related to the pharmacotherapy and this activities responsibilities seems to be transferred to others professional of the primary health care team.